2019
DOI: 10.1007/s10071-019-01282-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for discrimination between feeding sounds of familiar fish and unfamiliar mammal-eating killer whale ecotypes by long-finned pilot whales

Abstract: Killer whales (KW) may be predators or competitors of other cetaceans. Since their foraging behavior and acoustics differ among populations ('ecotypes'), we hypothesized that other cetaceans can eavesdrop on KW sounds and adjust their behavior according to the KW ecotype.We performed playback experiments on long-finned pilot whales (Globicephala melas) in Norway using familiar fish-eating KW sounds (fKW) simulating a sympatric population that might compete for foraging areas, unfamiliar mammal-eating KW sounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 94 publications
(146 reference statements)
0
15
0
Order By: Relevance
“…Killer whales present in the area are mostly fish-eating killer whales which might not represent a predator threat for sperm whales. Sperm whales may be able to discriminate acoustically between mammal-eating and fish-eating killer whales as has been shown in other marine mammal species (pinnipeds: [50]; cetaceans: [43,51]). If not perceived as a risk of predation, the presence of blackfish species might still represent a type of threat associated to the competing interest with sympatric species to exploit of the same habitat [43].…”
Section: Responses Related To Blackfish Presencementioning
confidence: 79%
See 3 more Smart Citations
“…Killer whales present in the area are mostly fish-eating killer whales which might not represent a predator threat for sperm whales. Sperm whales may be able to discriminate acoustically between mammal-eating and fish-eating killer whales as has been shown in other marine mammal species (pinnipeds: [50]; cetaceans: [43,51]). If not perceived as a risk of predation, the presence of blackfish species might still represent a type of threat associated to the competing interest with sympatric species to exploit of the same habitat [43].…”
Section: Responses Related To Blackfish Presencementioning
confidence: 79%
“…Sperm whales may be able to discriminate acoustically between mammal-eating and fish-eating killer whales as has been shown in other marine mammal species (pinnipeds: [50]; cetaceans: [43,51]). If not perceived as a risk of predation, the presence of blackfish species might still represent a type of threat associated to the competing interest with sympatric species to exploit of the same habitat [43]. Moreover, it could be that both blackfish species, i.e., pilot whales and killer whales, that we were not always able to distinguish, lead to different behavioral responses and that they influenced the response to sonar differently.…”
Section: Responses Related To Blackfish Presencementioning
confidence: 79%
See 2 more Smart Citations
“…Eavesdropping in cetaceans has been poorly studied, relatively to terrestrial animals. Most studies focussed on heterospecific cetacean dyads, especially predator-prey systems, demonstrating the importance of sound eavesdropping in the mediation of interspecific interactions (Fish and Vania 1971;Cummings and Thompson 1971;Tyack et al 2011;Curé et al 2013Curé et al , 2015Curé et al , 2019Bowers et al 2018;Benti et al 2021). Regarding the acousticallymediated interactions within species, some pioneering studies using playbacks on cetacean species were conducted in the humpback whale (Tyack 1981(Tyack , 1983Mobley et al 1988), the right whale (Clark and Clark 1980;Parks 2003) and the killer whales (Filatova et al 2011) and showed that the detection of conspecific sounds could trigger behavioural responses.…”
Section: Introductionmentioning
confidence: 99%